The Role of Islamic Religious Education Teachers in Ad-dressing Cyberbullying : A Study at Al-Islam Krian High School (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to identify and describe the role of Islamic Education (PAI) teachers in addressing cases of cyberbullying at SMA Al-Islam Krian, as well as to evaluate the effectiveness of the strategies implemented in its prevention and handling. The research employed a descriptive qualitative method, with data collected through observation, in-depth interviews, and documentation. The findings reveal that PAI teachers serve not only as educators but also as moral guides and motivators who instill Islamic values through personal approaches, digital ethics education, and the reinforcement of students' religious character. The strategies implemented include integrating religious values into the learning process, using religious activities to shape character, and participating in conflict mediation among students. Challenges faced include limited digital literacy among teachers, insufficient school policy support, and a lack of awareness among students and parents regarding the impact of cyberbullying. The study concludes that the role of PAI teachers is highly strategic and should be strengthened through training, supportive policies, and collaboration with various stakeholders to create a safe and morally grounded school environment .